SUSTAINABILITY OF EDUCATION IN POST-PANDEMIC: CHALLENGES AND OPPORTUNITY - Aria Cakra Wibawa; Bambang Suharjo (International Journal of Educational Management and Innovation, 2021)
The pandemic around the world has been going on for more than a year. A major impact in education has been the change from conventional education to online information technology-based education. After the pandemic, it was necessary to plan the educational model that was carrying out. To examine the educational model in the Indonesian Navy after the pandemic, a combination of SWOT - AHP will be carried out. The research subjects included five middle-ranking officers in the Indonesian Navy educational institution and the Indonesian Navy Education Office. The result of the research is that the Indonesian Navy needs to integrate the online-based education model with face-to-face education. Online-based education, especially in theory and face-to-face learning in the discussion model, workgroup, and teamwork in military team formations, platoons, company, battalion, and skills training in using the equipment. The global strategy compiled is an intensification of the combination of online and offline learning with an increasingly advanced educational information system, combining teaching materials and being equipped with increasingly qualified teaching staff from within the Indonesian Navy and others to improve Indonesian Navy education while maintaining system security and improve HR capabilities in the IT field by collaborating with other relevant agencies